Linguistic Weakening of Nasa-Yuwe in the Path Yu’ Community (Cauca, Colombia) - Uribe Muñoz, Cristian Mauricio (Íkala, Revista de Lenguaje y Cultura, 2025)
This article analyses the weakening of the Nasa-Yuwe language among the Path Yu’ community members, who settled in Cajibío, Cauca, Colombia. A mixed-methods approach with a qualitative dominant focus was followed, with interviews, focus groups, participant observation, and sociolinguistic surveys as data gathering tools. Findings show that Nasa-Yuwe language is severely weakened, with 60.5% of the population being bilingual in Nasa-Yuwe and Spanish, and Spanish being the dominant language. Interaction in Nasa-Yuwe language was observed to be limited across the territory. Only among older adults is Nasa-Yuwe predominant, while Spanish is dominant among adults and youth. The analysis showed that migration was the main reason for linguistic displacement. The arrival of the Nasa Indigenous people in the receiving area created contact with Spanish-speaking farmers, who showed rejection and discrimination towards indigenous language communities, leading to unfavorable linguistic attitudes toward their own language among the Indigenous people. This complex situation affects Nasa-Yuwe language intergenerational transmission. According to the language vitality scale of the Endangered Languages Catalog, Nasa-Yuwe in Path Yu’ is classified as severely endangered.